Design and Multi-Stage Assessment of a Rigid–Flexible Hybrid Floating Bridge for Rapid Deployment and Maneuvering - Yunling Ye; Bowen Niu; Guanxi Guo; Jiale Zhang; Jiayi Liu; Weide Wang; Mengzhen Li (Journal of Marine Science and Engineering, 2026)
Rapidly deployable floating bridges face coupled challenges in compact deployment, structural load-bearing, and controllable module maneuvering, which cannot be fully evaluated through a single-stage structural or hydrodynamic assessment. To close this gap, this study proposes a rigid–flexible hybrid floating bridge composed of rigid deck plates, inflatable buoyancy bladders, scissor linkages, and integrated waterjet propulsors. A multi-stage assessment was conducted through inflation and calm-water maneuvering tests, gas–solid coupled finite-element analysis, and hydrodynamic and mooring simulations. The inflation experiment revealed three stages in the inflation process of the rigid–flexible specimen, including filling, transition, and pressurization stages. A remotely controlled scale model completed longitudinal, lateral, rotational, and compound motions, demonstrating the feasibility of module-level maneuvering under manual remote control. The finite-element results showed that increasing the initial internal pressure improved the load-bearing capacity and reduced local plastic deformation of the upper deck, while further improvement became limited above 70 kPa. Under the specified wave–current conditions, the ten-module assembly exhibited maximum mooring tension, horizontal displacement, and rotation of 34.7 kN, 0.276 m, and 5.525°, respectively. These results demonstrate the potential of the proposed configuration for bearing capacity, rapid deployment, and resistance to the investigated current and wave conditions while providing a multi-stage framework for further engineering design.